1998
DOI: 10.1111/j.0435-3676.1998.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of rock glaciers

Abstract: Rock glaciers, common in many alpine and polar regions, have poorly understood internal structure, dynamics, and origins. A renewal of interest in the climatic and geomorphic significance of these striking landforms has served to intensify a long-standing controversy surrounding the genesis of rock glaciers. The controversy, which began more than 30 years ago, has resolved into two primary viewpoints. One holds that rock glaciers form through a continuum of glacial to periglacial processes and encompass featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 43 publications
2
77
0
3
Order By: Relevance
“…Two main types are widely recognised: glacierderived rock glaciers, formed through the accumulation of melt-out debris on the surface of downwasting valley glaciers; and talus rock glaciers, produced through the downslope deformation of talus accumulations (Clark et al, 1998;Humlum, 1998a;Haeberli et al, 2006). Several studies have indicated that the distribution of active talus rock glaciers is constrained by both temperature and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Two main types are widely recognised: glacierderived rock glaciers, formed through the accumulation of melt-out debris on the surface of downwasting valley glaciers; and talus rock glaciers, produced through the downslope deformation of talus accumulations (Clark et al, 1998;Humlum, 1998a;Haeberli et al, 2006). Several studies have indicated that the distribution of active talus rock glaciers is constrained by both temperature and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Kirkbride (1989) proposes that variations in ice mass influx serve to unify a process continuum of deformational geomorphological features of mixed ice and debris composition. The implication of this process continuum is that glaciers can transition between rock glaciers, debris-covered glaciers and clean-ice glaciers through space or time as a result of the varying ice influx (Kirkbride, 1989;Ackert Jr., 1998;Clark et al, 1998). Accordingly, the extent of a debris cover varies inversely with the glacier mass balance, whereby the debris cover extent is governed by transport-dominant conditions (higher ice velocities and lower surface ablation) during periods of positive mass balance and ablation-dominant conditions (lower ice velocities and higher ablation) during periods of negative mass balance (Kirkbride, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios realizados desde los años 80, mediante sondeos geofísicos, perforaciones, registros térmicos, seguimientos dinámicos en superficie y profundidad, han mostrado la complejidad morfogenética de los glaciares rocosos. Hoy son mayoría los autores que admiten su complejidad, con complicadas relaciones espaciales y genéticas (Whalley y Azzizi, 1994, Hamilton y Whalley, 1995Clark et al, 1998;Krainer, 2002;Berger et al, 2004;Humlum et al, 2007;Ribolini et al, 2007), si bien, los estudios más detallados no muestran estructuras y dinámicas internas asociadas a procesos glaciares.…”
Section: Introductionunclassified